Dental Neglect Leading to Foreign Body in Tooth - Sharma, Akhilesh (Journal of Orofacial Research, 2013)
An 11 years old boy accompanied by a neighbor reported to the department with pain in the lower front teeth region. History and clinical and radiographic examination revealed dental neglect by the parent and a sewing needle in the root canal of the lower left central incisor. The tooth had to be extracted due to extensive crown fracture. Parents were counseled with an empathetic approach and motivated for further dental treatment needs in the child.